Mediasi Praktik Akuntansi Manajemen pada Pengaruh Literasi Keuangan Terhadap Kinerja Keuangan UMKM - Komang Tri Yasrawan; Kadek Mitananda Pradnya Nugraha; Komang Dandy Andriadi (Jurnal IAKP : Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2025)
This study aims to analyze the mediating role of management accounting practices in the relationship between financial literacy and the financial performance of MSMEs. The population in this study was 66,368 MSMEs in Buleleng Regency. The number of samples was determined using the Isaac and Michael table at a significance level of 5%, yielding a minimum sample size of 348 MSMEs. The respondents of this study were MSME owners. The data collection method used a questionnaire. Data were analyzed using the Structural Equation Modeling Partial Least Squares method with the help of the SmartPLS version 4 application. The study found that financial literacy and management accounting practices had a positive and significant effect on financial performance; financial literacy had a positive and significant effect on management accounting practices; and management accounting practices mediated the positive and significant effect of financial literacy on financial performance among MSMEs in Buleleng Regency. The results of the study strengthen the evidence that increasing financial literacy has both direct and indirect effects through the optimization of management accounting practices, a phenomenon that has not been widely reported in the literature.